Young Malaysians' blogging habits and a linguistic analysis of their use of English in their weblogs - Ong, Lok Tik (2016)
The size of the blogosphere has long been a contentious issue amongst people researching the social media as it cannot be accurately determined. Bodies (BlogPulse, BlogScope, Technorati, etc.) which used to track the growing phenomenon across the world were careful with their choice of words when reporting on its size, such as Sifry’s Technorati report which said, “On July 31, 2006, Technorati tracked its 50 millionth blog” (Sifry, 2006, August 6). However, as Rosenberg (2006, August 9) points out, “… it doesn’t really matter. There’s still a revolution going on.” This ‘revolution’ is dominated by young people and in Malaysia, it was found that 74% of the bloggers in Malaysia were below 25 years old (Windows Live Spaces, 2006) but there is limited study on the phenomenon of casual blogging amongst this age group in Malaysia and the use of English in the blogs. The current study contributes to this body of literature, drawing from works on blogging, linguistic analysis, identity, and varieties of English. It adopts the social-constructivist framework and postulates that blogging is a social action which causes the blogosphere to be in a state of constant revision where “individuals create their own subjective meanings of their experiences through interactions with each other and their surrounding environment” (Hartas, 2010:44). This study used mixed methods in order to answer the research questions using three instruments: survey, interview, and weblog analysis to yield the data needed to investigate the content and interactive blog communication of selected young Malaysian casual bloggers who blog in English. The survey data yielded information about their blogging habits and content; the interview data yielded information about their language learning endeavours which influenced their choice of language or varieties of language in their blogs; and the in-depth analysis of one blog yielded information on how language was used in the blog to achieve communicative intent. The findings reveal the blogging habits of young Malaysian bloggers, and how their attitude towards their identity as Malaysians using English and socio-cultural factors influence their choice of language and/or varieties of English in their blog communication. It discovers the unconventional manner of using an existing language to achieve communicative intent among those in the same blogospheric region. This study makes both the bloggers and their blog texts the focus of its research.